Building better rechargeable Zn–Mn batteries with a highly active Mn3O4/carbon nanowire cathode and neutral Na2SO4/MnSO4 electrolyte. Issue 77 (5th September 2018) - Ma, Lai; Li, Linpo; Liu, Yani; Zhu, Jianhui; Meng, Ting; Zhang, Han; Jiang, Jian; Li, Chang Ming
Abstract : A more reliable/eco-friendly secondary Zn–Mn battery system is built with highly active Mn3 O4 @carbon nanowires and near-neutral electrolytes. Such configured batteries show high reversibility and superior behavior in terms of both stored capacity and cycling durability, holding great promise in near-future power-supply applications. Abstract : A more reliable/eco-friendly secondary Zn–Mn battery system is built with highly active Mn3 O4 @carbon nanowires and near-neutral electrolytes. Such configured batteries show high reversibility and superior behavior in terms of both stored capacity and cycling durability, holding great promise in near-future power-supply applications.